A Simple and Rapid Spectrophotometric Determination of Dapsone and its Dosage forms - Rami Reddy, N.; Sreedevi, G.; Prabhavathi, K.; Chakravarthy, I.E. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method was developed for estimation of dapsone. The method was based on the bromination of dapsone with a solution of excess brominating mixture. After bromination, the excess brominating mixture was treated with potassium iodide to obtain a yellow coloured solution. The absorbance of the yellow coloured solution was measured at 350 nm on Spectronic 1001 spectrophotometer against distilled water as blank. The method obeys Beer's law ranging from 40-200 μg/mL.